THE STATE ACCREDITATION OF HIGHER EDUCATION PROGRAMS REALIZED IN NETWORK FORM - Anton V. Dozhdikov (Moscow Polytechnic University, 2016)
The article considers the opportunities and prospects associated with the implementation the educational programs of higher education in the network form. Theincreased threats of imitation of educational activities for unscrupulous training providers are also discussed in this article. The review provides a range of problems and issues related to the assessment, examination and state accreditation of educational programs.